Facile synthesis and simulation of MnO2 nanoflakes on vertically aligned carbon nanotubes, as a high-performance electrode for Li-ion battery and supercapacitor. (10th September 2021) - Abdollahi, Ali; Abnavi, Amin; Ghasemi, Foad; Ghasemi, Shahnaz; Sanaee, Zeinab; Mohajerzadeh, Shams
Abstract: This study reports the successful fabrication of high-performance flexible binder-free lithium-ion battery anode and supercapacitor based on the synthesis of 3D hierarchical MnO2 nanoflakes (NFs) on vertically aligned carbon nanotubes (VACNTs) grown upon stainless steel (SS). The experimental results revealed that the prepared electrodes were well served as supercapacitors with a tremendous specific capacitance of MnO2 NFs VACNT/SS 1131 F/g at 0.25 A/g in 0.5 mol.L −1 Na2 SO4, 518.8% more than VACNT/SS (218 F/g). Compared to other MnO2 NFs/CNT composites, as-fabricated binder-free MnO2 NFs/VACNTs electrode achieves outstanding performance with high initial discharge and charge capacities of 2438 and 1289 mAhg −1 at a current density of 250 mAg −1, respectively. The fabricated anode anode further demonstrates an extraordinarily high reversible capacity of 803.2 mAhg −1 with columbic efficiency of 98.4% at a current density of 250 mAg −1 over 150 charge/discharge runs. Compared to pure VACNTs electrode, the MnO2 /VACNTs has significantly improved cycling stability and lithium storage capability, making this nanocomposite a promising anode for LIBs. Meanwhile, the electrochemical behavior of MnO2 NFs/VACNTs anode was evaluated using a numerical simulation approach. The simulation findings results showed excellent consistency between numerical and experimental results.